Utilization of Low Nitrogen Barley for Production of Distilling Quality Malt. (20th August 2020) - Black, Kirsty; Daute, Martina; Tziboula-Clarke, Athina; White, Philip J.; Iannetta, Pietro P. M.; Walker, Graeme
Abstract: The potential to utilize low nitrogen barley for production of distilling quality malt was studied. This presents an opportunity to reduce the environmental impact of nitrogen fertilizer applications. Malting barley (cv. Octavia) was grown without the application of inorganic nitrogen fertilizer, to produce grain with a relatively low nitrogen concentration (1.16%, dry weight basis). Following micro-malting trials, dextrinizing units (58 DU) obtained from low nitrogen malt were much higher than a typical specification of 45 DU for malt with a conventional nitrogen concentration (<1.5%). A higher soluble nitrogen ratio (SNR) or index of modification (IoM) of 49 indicated greater modification of the low nitrogen barley, resulting in higher extract released into the wort. Additionally, much lower levels of β-glucan were found in low nitrogen malt wort (64 mg/L compared with over 100 mg/L in wort of conventional nitrogen malt). Low nitrogen malt also produced higher predicted spirit yields following wort fermentation and wash distillation. These findings indicate that lower nitrogen concentration barley can be processed without negatively impacting malt quality for distilling applications. The implication of these findings to help realize more environmentally sustainable production of barley for malting and use in distilling is discussed.